A kind of alloy aluminum foil and its preparation method and application
By optimizing the alloy ratio and preparation process of aluminum foil, the problem of the existing battery aluminum foil has been solved, although the thickness of the aluminum foil is reduced but the mechanical properties are poor, the ultra-thinization and high energy density of the aluminum foil are achieved, and the rapid charging and discharge efficiency of the battery is improved.
Patent Information
- Application Number
- CN202411942551.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
Although the thickness of existing batteries is reduced, the mechanical properties and high resistance are poor, and the effect is poor for batteries, making it difficult to meet the needs of increasing energy density of new energy vehicle batteries and energy storage batteries.
By optimizing the selection and ratio of the smelting blank, the Al content in the aluminum foil is increased, the resistance is reduced, and the Fe, Si, Mn, Ti, Zn, Mg and Cu elements are introduced to form reinforced phases and refined grains, reduce microcracks, and improve the mechanical properties and conductivity of the aluminum foil, and the thickness of the aluminum foil is reduced to within 10μm.
The ultra-thinization of aluminum foil is achieved, which improves the energy density of the battery and the lithium ion transfer rate, significantly improves the fast charging and discharge efficiency, and ensures the high toughness and low resistance of aluminum foil.
Smart Images

Figure BDA0005214732150000131 
Figure BDA0005214732150000141 
Figure BDA0005214732150000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to an alloy aluminum foil and a preparation method and application thereof. Background Art
[0002] As resource and environmental issues become increasingly severe, a new energy revolution has been launched around the world. The new energy industry has also been listed as the first of the five emerging strategies in my country. Clean and efficient chemical power sources will inevitably grow faster and on a larger scale; electric vehicles and power-assisted vehicles are becoming the main driving force for the explosive growth of lithium-ion batteries. Lithium-ion batteries have good cycle performance, high energy density, high output voltage, and low self-discharge. They are widely used in 3C digital, energy storage, and automotive power. With the rapid development of electric vehicles powered by lithium-ion batteries, the requirements for the safety, rate performance, and energy performance of lithium-ion batteries are getting higher and higher.
[0003] As a current collector, aluminum foil mainly provides electron channels for electrochemical reactions, accelerates charge transfer, reduces electrochemical polarization, improves charge and discharge coulomb efficiency, and rarely participates in Li insertion and extraction reactions. It is a key material in the positive electrode of lithium batteries. With the continuous improvement of the energy density of new energy vehicle batteries and energy storage batteries, the market has put forward higher requirements for technical indicators such as the thinning of battery aluminum foil. At present, the thickness of aluminum foil for power batteries on the market has dropped from the initial 20μm to the current 12μm and 13μm. However, from the perspective of improving battery energy density, thinning is undoubtedly the development direction of power battery aluminum foil in the future. Therefore, it is urgent to develop a thinner aluminum foil for batteries to increase the energy density of batteries and better adapt to current development trends.
[0004] CN118976784A discloses a battery aluminum foil and a preparation method thereof, and relates to the technical field of battery aluminum foil. The preparation method is as follows: S1, hot rolling an aluminum foil blank to obtain an aluminum foil intermediate with a thickness of 3.5-4.1 mm; S2, cold rolling the aluminum foil intermediate for multiple passes under an ultrasonic vibration system with lubricating oil to obtain a foil-rolled blank with a thickness of 0.35-0.45 mm, wherein when the thickness of the intermediate pass is 0.6-0.9 mm after cold rolling, complete recrystallization annealing is performed under nitrogen protection, and the annealing temperature is 400-450°C; S3, foil rolling the foil-rolled blank to obtain an aluminum foil with a thickness of 0.01-0.015 mm; S4, corona treatment is performed on the aluminum foil, and then a modified coating is coated on the surface of the aluminum foil, and dried to obtain a battery aluminum foil.
[0005] CN118531263A discloses an aluminum foil for lithium ion batteries, the raw material components of which include, by mass percentage: Si: ≤0.04%, Fe: 0.14-0.18%, Cu: 0.03-0.05%, Mn: 0.01%, Mg: 0.01%, Cr: 0.01%, Zn: 0.01%, Ti: 0.015-0.025%, Ce: 0.01-0.03%, and the remainder is Al; the production method of the aluminum foil includes the following steps: melting, milling, soaking, hot rolling, cold rolling, and foil rolling.
[0006] Although the aluminum foil prepared by the above scheme has a low thickness, its mechanical properties are poor, its resistance is high, and its effect in batteries is poor. Summary of the invention
[0007] The object of the present invention is to provide an alloy aluminum foil and a preparation method and application thereof. The method of the present invention selects and optimizes the smelting blank, ensures the mechanical properties of the aluminum foil, reduces its resistance, increases the Al content in the finished aluminum foil, reduces the thickness of the aluminum foil to within 10μm, reduces the weight of the current collector, and converts this part of the space into electrode material for use, thereby increasing the energy density of the battery, accelerating the lithium ion transfer rate, and greatly improving the rapid charging and discharging efficiency.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing an alloy aluminum foil, the preparation method comprising the following steps:
[0010] (1) The following element mass ratios are used to prepare the mixed material, wherein Fe = 0.05% to 0.30%, for example, 0.05%, 0.05%, 0.1%, 0.2% or 0.3%, etc., not limited to the listed values, other values not listed in the numerical range are also applicable, Si = 0.02% to 0.15%, for example, 0.02%, 0.08%, 0.1%, 0.12% or 0.15%, etc. , not limited to the listed values, other values not listed in the numerical range are also applicable, Cu = 0.01% ~ 0.04%, for example: 0.01%, 0.02%, 0.03% or 0.04%, etc., not limited to the listed values, other values not listed in the numerical range are also applicable, Mn = 0.02 ~ 0.03%, for example: 0.02%, 0.022%, 0.025%, 0.028% or 0.03 %, etc., are not limited to the listed values, and other values not listed in the numerical range are also applicable, Zn = 0.02% ~ 0.04%, for example: 0.02%, 0.025%, 0.03%, 0.035% or 0.04%, etc., are not limited to the listed values, and other values not listed in the numerical range are also applicable, Mg = 0.0005% ~ 0.002%, for example: 0.0005%, 0.0008%, 0.001%, 0.0015% or 0.002%, etc., are not limited to the listed values, and other values not listed in the numerical range are also applicable, Ti = 0.01% ~ 0.04%, for example: 0.01%, 0.02%, 0.03% or 0.04%, etc., are not limited to the listed values, and other values not listed in the numerical range are also applicable, and the rest is Al, and the mixed material is smelted to obtain an alloy liquid;
[0011] (2) after degassing the alloy liquid, the degassed alloy liquid is subjected to cast-rolling treatment to obtain a parent coil;
[0012] (3) cold rolling the parent coil to obtain a rolled coil;
[0013] (4) performing intermediate annealing on the rolled coil to obtain a blank, and performing foil rolling on the blank to obtain the alloy aluminum foil.
[0014] The present invention improves the Al content in the finished aluminum foil by selecting and optimizing the smelting blank, and can reduce the resistance of the foil compared with the 1100 alloy. At the same time, by controlling the Fe and Si contents, the formation of coarse iron-rich phases is suppressed, the second phase grain size is made smaller, the source of microcracks is reduced, and the mechanical properties of the finished battery aluminum foil are improved; Mn and Ti elements are introduced to form a strengthening phase, increase the internal grain nucleation points, and achieve the purpose of grain refinement; Zn, Mg and Cu elements are introduced to increase the ductility of the blank, and then in the subsequent foil rolling process, even if the aluminum foil is rolled to less than 10μm, cracking and strip breakage will not occur.
[0015] Preferably, the Fe in step (1) is prepared using elemental iron.
[0016] Preferably, the Si in step (1) is prepared using elemental silicon.
[0017] Preferably, the Cu in step (1) is prepared using single element copper.
[0018] Preferably, the Mn in step (1) is prepared using elemental manganese.
[0019] Preferably, the Zn in step (1) is prepared using elemental zinc.
[0020] Preferably, the Ti in step (1) is prepared using single substance titanium.
[0021] Preferably, the Al in step (1) is prepared from high-purity aluminum ingots with a purity of ≥99.85%.
[0022] Preferably, the atmosphere of the smelting treatment in step (1) includes nitrogen and / or argon.
[0023] Preferably, the temperature of the smelting treatment in step (1) is 600°C to 730°C, for example, 600°C, 620°C, 650°C, 700°C or 730°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the smelting treatment time in step (1) is 30 min to 90 min, for example, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, after the smelting treatment in step (1), a refining agent is added, and the smelting is allowed to stand and slag is removed.
[0026] Preferably, the refining agent includes KCl, CaCl 2, NaCl or MgCl, any one or a combination of at least two thereof, typical but non-limiting combinations include a combination of KCl and NaCl, KCl and CaCl 2 or the combination of NaCl and MgCl, etc.
[0027] Preferably, the addition amount of the refining agent is 1kg / t to 4.5kg / t, for example, 1kg / t, 2kg / t, 3kg / t, 4kg / t or 4.5kg / t, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the temperature of the degassing treatment in step (2) is 670°C to 800°C, for example, 670°C, 700°C, 720°C, 750°C or 800°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the dehydrogenation standard of the degassing treatment in step (2) is ≤0.12 ml / 100 g·Al.
[0030] Preferably, the degassing treatment in step (2) is followed by filtration treatment.
[0031] Preferably, the filtration treatment includes plate filtration and / or tubular filtration.
[0032] Preferably, the pore size of the filter plate for the filtration treatment is 30 μm to 60 μm, for example, 30 μm, 35 μm, 40 μm, 50 μm or 60 μm, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the temperature of the casting roll in the casting and rolling treatment in step (2) is 60°C to 100°C, for example, 60°C, 70°C, 80°C, 90°C or 100°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] Preferably, the casting speed of the casting and rolling treatment in step (2) is 0.8m / min to 1.1m / min, for example: 0.8m / min, 0.85m / min, 0.9m / min, 1m / min or 1.1m / min, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the thickness of the mother roll in step (2) is 6 mm to 7.5 mm, for example, 6 mm, 6.5 mm, 6.8 mm, 7 mm or 7.5 mm, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0036] Preferably, rolling oil is added during the cold rolling process in step (3).
[0037] Preferably, the rolling oil comprises a base oil and additives.
[0038] Preferably, the base oil contains any one of alkanes, cycloalkanes, aromatic hydrocarbons or olefins, or a combination of at least two of them. Typical but non-limiting combinations of alkanes and cycloalkanes include a combination of , a combination of aromatic hydrocarbons and olefins, or a combination of cycloalkanes and aromatic hydrocarbons, etc.
[0039] Preferably, the additive contains any one of fatty acids, fatty alcohols or fatty acid esters or a combination of at least two thereof. Typical but non-limiting combinations include a combination of fatty acids and fatty acid esters, a combination of fatty alcohols and fatty acid esters, or a combination of fatty acids and fatty alcohols.
[0040] Preferably, in the rolling oil, the mass fraction of the additive is 1% to 10%, for example, 1%, 2%, 5%, 8% or 10%, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] Preferably, the light transmittance of the rolling oil is 90% to 96%, for example, 90%, 91%, 92%, 93%, 94%, 95% or 96%, etc., and is not limited to the listed values, and other unlisted values within the range are also applicable.
[0042] Preferably, the cold rolling process in step (3) is performed with 3 to 5 passes, for example, 3 passes, 4 passes or 5 passes.
[0043] Preferably, the rolling force of the cold rolling treatment in step (3) is 1100kN to 4300kN, for example: 1100kN, 1500kN, 2000kN, 3000kN or 4300kN, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the rolling speed of the cold rolling treatment in step (3) is 400m / min to 600m / min, for example: 400m / min, 450m / min, 500m / min, 550m / min or 600m / min, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Preferably, the thickness of the rolled coil in step (3) is 0.2 mm to 0.36 mm, for example, 0.2 mm, 0.25 mm, 0.28 mm, 0.3 mm or 0.36 mm, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0046] Preferably, the temperature of the intermediate annealing in step (4) is 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C or 500°C, etc., and is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0047] Preferably, the intermediate annealing time in step (4) is 20 h to 30 h, for example, 20 h, 22 h, 25 h, 28 h or 30 h, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0048] Preferably, the foil rolling process in step (4) is performed with 4 to 5 passes, for example, 4 or 5 passes.
[0049] Preferably, the rolling force of the foil rolling process in step (3) is 1000kN to 3500kN, for example: 1000kN, 1500kN, 2000kN, 2500kN, 3000kN or 3500kN, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the rolling speed of the foil rolling process in step (3) is 400 m / min to 1300 m / min, for example 400 m / min, 500 m / min, 800 m / min, 1000 m / min or 1300 m / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In a second aspect, the present invention provides an alloy aluminum foil, which is prepared by the preparation method described in the first aspect;
[0052] The thickness of the aluminum foil is 8 μm to 10 μm, for example, 8 μm, 8.5 μm, 9 μm, 9.5 μm or 10 μm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0053] The method of the present invention can produce ultra-thin aluminum foil with a thickness of less than 10 μm, which greatly reduces the cost. When the thickness of the positive electrode collector aluminum foil is reduced from 12 μm to 10 μm, the volume space occupancy of the battery cell is increased, and the application space of the electrode material can be correspondingly increased, which is ultimately reflected in an increase of more than 0.55% in the energy density of the battery cell.
[0054] In a third aspect, the present invention provides a battery, comprising the alloy aluminum foil as described in the second aspect.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) The method of the present invention increases the Al content in the finished aluminum foil by selecting and optimizing the smelting blank, while reducing the thickness of the aluminum foil to less than 10 μm, thereby reducing the weight of the current collector and converting this space into electrode material for use, thereby increasing the energy density of the battery and accelerating the lithium ion transfer rate, thereby greatly improving the rapid charge and discharge efficiency.
[0057] (2) In the technical solution of the present invention, the alloy ratio is optimized to maintain a stable value for the second phase content of the aluminum foil, while the crystal size does not change. The first phase, which plays a leading role, has fine grains that can improve the uniformity of the grain size and strengthen the mechanical properties of the material; the degassing temperature is increased to make it easier to dissolve and remove the hydrogen and oxidized slag in the adsorbed melt, ensuring that the impurities in the aluminum melt are melted more thoroughly, which can effectively improve the toughness of the aluminum foil. Extending the intermediate annealing time can effectively ensure that the deformation texture generated by the rolling force during the rolling process of the aluminum foil is more thoroughly recrystallized, effectively improving the uniformity of the organization and strengthening the tensile elongation properties of the aluminum foil. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0059] The Fe described in the embodiments and comparative examples of the present invention is prepared using simple iron, the Si is prepared using simple silicon, the Cu is prepared using simple copper, the Mn is prepared using simple manganese, the Zn is prepared using simple zinc, the Ti is prepared using simple titanium, and the Al is prepared using a high-purity aluminum ingot with a purity of ≥99.85%.
[0060] In the examples and comparative examples of the present invention, the content of impurities is extremely low and therefore not shown.
[0061] Example 1
[0062] This embodiment provides an alloy aluminum foil, which is prepared by the following method:
[0063] (1) preparing a mixed material according to the following element mass ratio, wherein Fe=0.15%, Si=0.04%, Cu=0.03%, Mn=0.025%, Zn=0.03%, Mg=0.001%, Ti=0.025%, and the rest is Al, smelting the mixed material at 650° C. for 60 min in an argon atmosphere, adding NaCl in an amount of 2 kg / t after smelting, and obtaining an alloy liquid after standing and slagging;
[0064] (2) After the alloy liquid is degassed at 750°C, the dehydrogenation standard is: ≤0.12 ml / 100 g·Al, and filtered through a filter plate with a pore size of 40 μm, the alloy liquid is cast and rolled at 80°C at a speed of 1 m / min to obtain a mother coil with a thickness of 7 mm;
[0065] (3) rolling the mother coil on a cold rolling mill, adding rolling oil for lubrication, the rolling oil comprising 95% of an alkane-containing base oil and 5% of a fatty acid additive, the light transmittance of the rolling oil being controlled between 90% and 96%, rolling 4 times, the rolling force being 3000 kN, the rolling speed being 500 m / min, and obtaining a rolled coil with a thickness of 0.25 mm;
[0066] (4) The rolled coil was subjected to intermediate annealing treatment at 400° C. for 25 h to obtain a billet, and the billet was subjected to foil rolling treatment for 5 times at a speed of 800 m / min under a rolling force of 2000 kN to obtain an alloy aluminum foil with a thickness of 10 μm.
[0067] Example 2
[0068] This embodiment provides an alloy aluminum foil, which is prepared by the following method:
[0069] (1) preparing the mixture according to the following element mass ratio, wherein Fe=0.05%, Si=0.02%, Cu=0.01%, Mn=0.02%, Zn=0.02%, Mg=0.0005%, Ti=0.01%, and the rest is Al, smelting the mixture in an argon atmosphere at 600° C. for 90 min, adding KCl in an amount of 1 kg / t after smelting, and obtaining an alloy liquid after standing and slagging;
[0070] (2) After the alloy liquid is degassed at 670°C, the dehydrogenation standard is: ≤0.12 ml / 100 g·Al, and filtered through a filter plate with a pore size of 30 μm, the alloy liquid is cast and rolled at 100°C at a speed of 1.1 m / min to obtain a mother coil with a thickness of 6 mm;
[0071] (3) rolling the mother coil on a cold rolling mill, adding rolling oil for lubrication, the rolling oil comprising 95% of an alkane-containing base oil and 5% of a fatty acid additive, the light transmittance of the rolling oil being controlled between 90% and 96%, rolling for 3 passes, the rolling force being 4300 kN, the rolling speed being 600 m / min, and obtaining a rolled coil with a thickness of 0.2 mm;
[0072] (4) The rolled coil was subjected to intermediate annealing treatment at 500° C. for 30 h to obtain a billet, and the billet was subjected to foil rolling treatment for 5 times at a speed of 1300 m / min under a rolling force of 3500 kN to obtain an alloy aluminum foil with a thickness of 8 μm.
[0073] Example 3
[0074] This embodiment provides an alloy aluminum foil, which is prepared by the following method:
[0075] (1) preparing a mixed material according to the following element mass ratio, wherein Fe=0.3%, Si=0.15%, Cu=0.04%, Mn=0.03%, Zn=0.04%, Mg=0.002%, Ti=0.04%, and the rest is Al, smelting the mixed material in an argon atmosphere at 730° C. for 30 min, adding KCl in an amount of 4.5 kg / t after smelting, and obtaining an alloy liquid after standing and slagging;
[0076] (2) After the alloy liquid is degassed at 800°C, the dehydrogenation standard is: ≤0.12 ml / 100 g·Al, and filtered through a filter plate with a pore size of 60 μm, the alloy liquid is cast and rolled at 100°C at a speed of 1.1 m / min to obtain a mother coil with a thickness of 7.5 mm;
[0077] (3) rolling the mother coil on a cold rolling mill, adding rolling oil for lubrication, the rolling oil comprising 95% of an alkane-containing base oil and 5% of a fatty acid additive, the light transmittance of the rolling oil being controlled between 90% and 96%, rolling 4 times, the rolling force being 1100 kN, the rolling speed being 400 m / min, and obtaining a rolled coil with a thickness of 0.36 mm;
[0078] (4) The rolled coil was subjected to intermediate annealing treatment at 300° C. for 20 h to obtain a billet, and the billet was subjected to foil rolling treatment for 5 times at a speed of 400 m / min under a rolling force of 1000 kN to obtain an alloy aluminum foil with a thickness of 10 μm.
[0079] Example 4
[0080] The only difference between this embodiment and embodiment 1 is that the temperature of the degassing treatment is 650° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0081] Example 5
[0082] The only difference between this embodiment and embodiment 1 is that the temperature of the degassing treatment is 850° C., and the other conditions and parameters are exactly the same as those in embodiment 1.
[0083] Example 6
[0084] The only difference between this embodiment and embodiment 1 is that the intermediate annealing time is 15 hours, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0085] Comparative Example 1
[0086] The only difference between this comparative example and Example 1 is that Fe=0.5%, and the other conditions and parameters are exactly the same as those in Example 1.
[0087] Comparative Example 2
[0088] The only difference between this comparative example and Example 1 is that Si=0.2%, and the other conditions and parameters are exactly the same as those in Example 1.
[0089] Comparative Example 3
[0090] The only difference between this comparative example and Example 1 is that Mn=0.01%, and the other conditions and parameters are exactly the same as those in Example 1.
[0091] Comparative Example 4
[0092] The only difference between this comparative example and Example 1 is that Mn=0.04%, and the other conditions and parameters are exactly the same as those in Example 1.
[0093] Comparative Example 5
[0094] The only difference between this comparative example and Example 1 is that Zn=0.01%, and the other conditions and parameters are exactly the same as those in Example 1.
[0095] Comparative Example 6
[0096] The only difference between this comparative example and Example 1 is that Zn=0.05%, and the other conditions and parameters are exactly the same as those in Example 1.
[0097] Comparative Example 7
[0098] The only difference between this comparative example and Example 1 is that Ti=0.005%, and the other conditions and parameters are exactly the same as those in Example 1.
[0099] Comparative Example 8
[0100] The only difference between this comparative example and Example 1 is that Ti=0.05%, and the other conditions and parameters are exactly the same as those in Example 1.
[0101] Comparative Example 9
[0102] The only difference between this comparative example and Example 1 is that Mg=0.0001%, and the other conditions and parameters are exactly the same as those in Example 1.
[0103] Comparative Example 10
[0104] The only difference between this comparative example and Example 1 is that Mg=0.003%, and the other conditions and parameters are exactly the same as those in Example 1.
[0105] Comparative Example 11
[0106] The only difference between this comparative example and Example 1 is that no degassing treatment is performed, and other conditions and parameters are exactly the same as those in Example 1.
[0107] Comparative Example 12
[0108] The only difference between this comparative example and Example 1 is that the thickness of the alloy aluminum foil is controlled at 12 μm, and the other conditions and parameters are exactly the same as those in Example 1.
[0109] Performance Testing:
[0110] Foil resistance test: Cut the prepared aluminum foil into a size of 30×30 mm, and use a four-probe resistance meter to test the foil resistance R1.
[0111] Number of belt breaks during rolling for 10,000 m: The belt break data during rolling of the finished aluminum foil obtained in the same embodiment or comparative example is simulated, and the number of belt breaks occurring in 100 experimental results is statistically analyzed by probability, and the number of belt breaks during rolling for 10,000 m is obtained. Since it is a probability statistic, it is converted to 10,000 m and then multiplied by 100, so it is a multiple of 10.
[0112] 25℃ discharge performance:
[0113] a. Under 25±2℃, place for 10 minutes and cycle the battery at 0.5C / 0.5C for 5 weeks;
[0114] b. The battery is charged at 0.5C constant current and constant voltage;
[0115] c. Leave the battery at 25±2℃ for 10 minutes;
[0116] d. Discharge at 3C current until the battery voltage reaches 2.0V;
[0117] e. Record the discharge capacity of the battery cell, calculate the discharge gram capacity, discharge energy efficiency, etc.
[0118] 0℃ discharge performance
[0119] a. Under 25±2℃, place for 10 minutes and cycle the battery at 0.5C / 0.5C for 5 weeks;
[0120] b. The battery is charged at 0.5C constant current and constant voltage;
[0121] c. The battery is placed at 0±2℃ for 2h;
[0122] d. Discharge at 1C current until the battery voltage reaches 2.0V;
[0123] e. Record the discharge capacity of the battery cell, calculate the discharge gram capacity, discharge energy efficiency, etc.
[0124] According to GB / T16865 standard for tensile test specimens and methods for deformed aluminum, magnesium and their alloy products, the alloy aluminum foils of the embodiments and comparative examples were subjected to tensile tests. The test parameters were tensile strip 15 mm × 100 mm, chuck speed 50 mm / min, and clamp spacing 70 mm. The test results are shown in Table 1:
[0125] Table 1
[0126]
[0127]
[0128] The alloy aluminum foils obtained in the embodiment and the comparative example were made into 1650mAh soft-pack batteries according to the standard, and the electrical performance data were tested. The test results are shown in Table 2:
[0129] Table 2
[0130]
[0131] As can be seen from Table 1-2, from Examples 1-6, the tensile strength of the alloy aluminum foil prepared by the method of the present invention can reach more than 224.53MPa, the elongation can reach more than 3.53%, the resistance can reach less than 6.9mΩ, and the effect of continuous belting of 10,000 meters can be achieved, which greatly improves the production yield. The pole piece elongation rate can reach more than 0.52%, and the discharge capacity of the manufactured battery cell can reach more than 1649.98mAh / g. The 3C discharge energy efficiency at 25°C can reach more than 72.34%, and the 1C discharge energy efficiency at 0°C can reach more than 89.66%. The alloy ratio has a great influence on the mechanical properties of the aluminum foil. The present invention controls the alloy ratio to form a strengthening phase and performs a degassing treatment during the smelting process, so as to effectively reduce impurities in the aluminum foil and improve the toughness of the finished aluminum foil, that is, the tensile elongation is improved.
[0132] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the alloy aluminum foil of the present invention, the temperature of the degassing treatment will affect its performance. When the temperature of the degassing treatment is controlled at 670°C to 800°C, the performance of the alloy aluminum foil is better. If the temperature of the degassing treatment is too low, the inorganic metal impurities in the aluminum melt are difficult to be dissolved a second time, thereby forming a stress short plate in the aluminum ingot, and the aluminum foil is prone to breakage when subjected to stress. If the temperature of the degassing treatment is too high, the aluminum phase in the aluminum liquid will further form a second phase with other metals, causing the grain size to increase, thereby reducing the toughness of the aluminum foil.
[0133] By comparing Example 1 and Example 6, it can be seen that in the preparation process of the alloy aluminum foil of the present invention, the time of the intermediate annealing treatment will affect its performance. When the time of the intermediate annealing treatment is controlled to be more than 20 hours (the effect will not be better if the time is too long, but the energy consumption will increase), the performance of the alloy aluminum foil obtained is better. If the time of the intermediate annealing treatment is too short, the internal grains of the aluminum foil are elongated due to the rolling force in the intermediate process, and the deformed structure produced cannot be completely recrystallized, which reduces the uniformity of the aluminum foil's structure and further reduces the tensile elongation performance.
[0134] By comparing Example 1 with Comparative Examples 1-2, it can be seen that in the preparation process of the alloy aluminum foil of the present invention, Fe is controlled at 0.05% to 0.30%, and Si is controlled at 0.02% to 0.15%, and the effect of preparing the alloy aluminum foil is better. If the addition amount of Fe and Si is too high, on the one hand, the amount of the as-cast second phase is significantly increased, especially the coarse needle-like FeAl 3 A large increase in the phase is also extremely harmful to the performance; on the other hand, the increase in the Fe content in the material will also cause an increase in the solid solution Fe content, thereby increasing the work hardening rate, resulting in a reduction in the toughness of the aluminum foil, that is, a reduction in the tensile elongation performance.
[0135] By comparing Example 1 with Comparative Examples 3-4, it can be seen that in the preparation process of the alloy aluminum foil of the present invention, Mn is controlled at 0.02% to 0.03%, and the effect of preparing the alloy aluminum foil is better. If the amount of Mn added is too low, the amount of Al-Mn strengthening phase generated is limited, so that the first phase (aluminum phase) plays a leading role. If the amount of Mn added is too high, the excess Mn is easy to form Al with Al. 6 Mn strengthening phase has high strength, but it precipitates in the form of short flakes during the alloy recrystallization process. Due to its brittleness, it can easily become a source of fracture during the tensile process.
[0136] By comparing Example 1 and Comparative Examples 5-6, it can be seen that in the preparation process of the alloy aluminum foil of the present invention, Zn is controlled at 0.02% to 0.04%, and the effect of obtaining the alloy aluminum foil is better. If the Zn addition amount is too low, a trace strengthening phase can be formed. If the Zn addition amount is too high, a large number of strengthening phases will increase the brittleness of the aluminum foil and reduce the toughness.
[0137] By comparing Example 1 with Comparative Examples 7-8, it can be seen that in the preparation process of the alloy aluminum foil of the present invention, Ti is controlled at 0.01% to 0.04%, and the effect of preparing the alloy aluminum foil is better. If the Ti addition amount is too low, as an element for refining grains, TiAl 3Phase, as the heterogeneous core of alloy grain nucleation, increases the number of crystal nuclei, increases the number of grains, and then refines the grains. If the Ti addition is too high, the grains will coarsen and a segregated phase will appear at the grain boundaries. At this time, the heterogeneous crystal nucleus TiAl3 is already in far more supply than demand, and begins to precipitate in large quantities and segregate, and the heterogeneous nucleation effect is weakened, so that the grain size of the aluminum foil becomes larger, the number of grain boundaries decreases, and finally the tensile elongation performance decreases.
[0138] From the comparison between Example 1 and Comparative Examples 9-10, it can be seen that in the preparation process of the alloy aluminum foil of the present invention, Mg is controlled at 0.0005% to 0.002%, and the effect of preparing the alloy aluminum foil is better. If the Mg addition amount is too low, α(Al 3 Mg 2 ) is a small number, and has little strengthening effect on the material. If the Mg addition is too high, the Mg element is excessive, which makes it easy for Si elements to combine with Mg elements to form Mg 2 Si phase reduces the solubility of Mg in the matrix, resulting in a decrease in tensile strength and elongation.
[0139] From the comparison between Example 1 and Comparative Example 11, it can be seen that in the preparation process of the alloy aluminum foil of the present invention, the gas and impurities in the aluminum liquid are separated by a physical method after degassing treatment to achieve the purpose of purifying the aluminum liquid. The specific method includes using a rotating rotor to break the nitrogen or argon gas blown into the aluminum melt into a large number of dispersed bubbles, which absorb hydrogen and oxidized slag in the melt and are taken out of the melt surface as the bubbles rise, thereby purifying the melt, thereby ensuring that the toughness of the subsequent finished aluminum foil is improved.
[0140] By comparing Example 1 and Comparative Example 12, it can be seen that the alloy aluminum foil of the present invention is controlled within 10μm, and the aluminum foil elongation rate is greatly increased by 42%. It can adapt to the rolling elongation difference between the pole ear and the positive electrode membrane, improve the broken belt, and provide production yield. The standard capacity of 1650mAh soft-pack battery cell is used for design. It can be found that the internal space occupancy rate can be reduced by 0.55%, that is, the battery active material space can be increased, which promotes the energy density to increase by 0.55%. At the same time, after the current collector is thinned, the rapid transfer of lithium ions can be achieved, thereby improving the rapid charge and discharge performance of the material. It can be seen from the table that at 25°C, the energy efficiency of 10μm can be increased to 72.38% under 3C rate discharge, and at 0°C, the energy efficiency is increased by 2.24% under 1C rate discharge.
[0141] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing an alloy aluminum foil, characterized in that: The preparation method comprises the following steps: (1) preparing materials according to the following element mass ratio to obtain a mixed material, wherein Fe=0.05%-0.30%, Si=0.02%-0.15%, Cu=0.01%-0.04%, Mn=0.02%-0.03%, Zn=0.02%-0.04%, Mg=0.0005%-0.002%, Ti=0.01%-0.04%, and the rest is Al, and smelting the mixed material to obtain an alloy liquid; (2) after degassing the alloy liquid, the degassed alloy liquid is subjected to cast-rolling treatment to obtain a parent coil; (3) cold rolling the parent coil to obtain a rolled coil; (4) performing intermediate annealing on the rolled coil to obtain a blank, and performing foil rolling on the blank to obtain the alloy aluminum foil.
2. The preparation method according to claim 1, characterized in that The Fe in step (1) is prepared by single substance iron; Preferably, the Si in step (1) is prepared using elemental silicon; Preferably, the Cu in step (1) is prepared using single element copper; Preferably, the Mn in step (1) is prepared using elemental manganese; Preferably, the Zn in step (1) is prepared using elemental zinc; Preferably, the Ti in step (1) is prepared using single substance titanium; Preferably, the Al in step (1) is prepared from high-purity aluminum ingots with a purity of ≥99.85%.
3. The preparation method according to claim 1 or 2, characterized in that: The atmosphere of the smelting treatment in step (1) includes nitrogen and / or argon; Preferably, the temperature of the smelting treatment in step (1) is 600° C. to 730° C.; Preferably, the smelting treatment time in step (1) is 30 min to 90 min; Preferably, after the smelting treatment in step (1), a refining agent is added, and the smelting is allowed to stand and slag is removed; Preferably, the refining agent comprises any one or a combination of at least two of KCl, CaCl2, NaCl or MgCl; Preferably, the addition amount of the refining agent is 1 kg / t to 4.5 kg / t.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The temperature of the degassing treatment in step (2) is 670°C to 800°C; Preferably, the dehydrogenation standard of the degassing treatment in step (2) is ≤0.12 ml / 100 g·Al; Preferably, the degassing treatment in step (2) is followed by filtering treatment; Preferably, the filtration treatment includes plate filtration and / or tube filtration; Preferably, the pore size of the filter plate in the filtration treatment is 30 μm to 60 μm.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the casting rolls in the casting and rolling process in step (2) is 60° C. to 100° C. Preferably, the casting speed of the casting process in step (2) is 0.8 m / min to 1.1 m / min; Preferably, the thickness of the mother roll in step (2) is 6 mm to 7.5 mm.
6. The preparation method according to any one of claims 1 to 5, characterized in that: Adding rolling oil during the cold rolling process in step (3); Preferably, the rolling oil comprises a base oil and an additive; Preferably, the base oil contains any one or a combination of at least two of alkanes, cycloalkanes, aromatic hydrocarbons or olefins; Preferably, the additive contains any one or a combination of at least two of fatty acids, fatty alcohols or fatty acid esters; Preferably, in the rolling oil, the mass fraction of the additive is 1% to 10%; Preferably, the light transmittance of the rolling oil is 90% to 96%; Preferably, the cold rolling process in step (3) is performed 3 to 5 times; Preferably, the rolling force of the cold rolling process in step (3) is 1100 kN to 4300 kN; Preferably, the rolling speed of the cold rolling treatment in step (3) is 400 m / min to 600 m / min; Preferably, the thickness of the rolled coil in step (3) is 0.2 mm to 0.36 mm.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature of the intermediate annealing in step (4) is 300° C. to 500° C.; Preferably, the intermediate annealing time in step (4) is 20 h to 30 h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The number of rolling passes of the foil rolling process in step (4) is 4 to 5; Preferably, the rolling force of the foil rolling process in step (3) is 1000 kN to 3500 kN; Preferably, the rolling speed of the foil rolling process in step (3) is 400 m / min to 1300 m / min.
9. An alloy aluminum foil, characterized in that: The alloy aluminum foil is prepared by the preparation method according to any one of claims 1 to 8; The thickness of the aluminum foil is 8 μm to 10 μm.
10. A battery, characterized in that: The battery comprises the alloy aluminum foil as claimed in claim 9.